2017
DOI: 10.3126/kumj.v13i2.16785
|View full text |Cite
|
Sign up to set email alerts
|

Can Laparoscopic Cholecystectomy be a Feasible Standard in a Rural set up too? - An Experience of 348 cases from a Peripheral set up of Western Nepal

Abstract: Background Gall stone disease is a common reason for admissions in both acute and elective situations and bears significant morbidity in the rural population of western Nepal. The earlier conventional open method of treatment for the same seems to have been largely seeded by the laparoscopic approach owing to its numerous benefits.Objective To study the clinical profile of patients with symptomatic gall stones with respect to demography and to assess the feasibility of using Laparoscopic cholecystectomy as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…11 In another study by Kumar et.al from Utarpardesh India shows a conversion rate of 4.5% 12 and another study from Palpa, Nepal shows a conversion rate of 6.9%. 13 When we compared our conversion rate to the local and international literature we found that our conversion rate was far less than the local and international eviedence available. We may attribute our low conversion rate to our experienced and well trained team.…”
Section: Discussionmentioning
confidence: 97%
“…11 In another study by Kumar et.al from Utarpardesh India shows a conversion rate of 4.5% 12 and another study from Palpa, Nepal shows a conversion rate of 6.9%. 13 When we compared our conversion rate to the local and international literature we found that our conversion rate was far less than the local and international eviedence available. We may attribute our low conversion rate to our experienced and well trained team.…”
Section: Discussionmentioning
confidence: 97%
“…The study suggested that basic laparoscopic procedures could be offered safely to resource-poor rural population. Shrestha AL, et al 26 2015 Nepal…”
Section: Nigeriamentioning
confidence: 99%
“…A study reports an overall prevalence of 4.78% in Nepal 12 . On the one hand, Cholelithiasis can result to several complications, including cholecystitis (inflammation of the gallbladder) and cholangitis (inflammation of the bile duct) 7 .On the other hand , irrational prescribing pattern acts as a contributing factor towards ineffective, unsafe and costly treatment, increased evidence of adverse drug reaction, exacerbation of mortality & morbidity 13 .Laparoscopic cholecystectomy which was introduced in the early 90s, which is considered a safe treatment for Gall bladder disease, but still unjustified increase in surgical procedures has been observed 14 . There seems to be a significant number of hospital admissions in our country annually due to gallstones and its related complications 9 but there are very few studies done in Nepal 5 . This study will help to analyze the prescribing pattern of medicines among cholelithiasis in-patients of surgery ward which might help in further management of disease. Furthermore, it will also help medical & paramedical students and other people in knowing about different kinds of medications used during hospitalization and after discharge for its management strategy.…”
Section: Introductionmentioning
confidence: 99%